Jews and Humor (Purdue University Press, 2007)
Jews and humor is, for most people, a natural and felicitous collocation. In spite of, or perhaps because of, a history of crises and living on the edge, Jews have often created or resorted to humor. But what is “humor”? And what makes certain types, instances, or performances of humor “Jewish”? These are among the myriad queries addressed by the fourteen authors whose essays are collected in this volume. And, thankfully, their observations, always apt and often witty, are expressed with a lightness of style and a depth of analysis that are appropriate to the many topics they cover. The chronological range of these essays is vast: from the Hebrew Bible to the 2000s, with many stops in between for Talmudic texts, medieval parodies, eighteenth-century joke books, and twentieth-century popular entertainment. The subject matter is equally impressive. In addition to rounding up many of the “usual suspects,” such as Woody Allen, the Marx Brothers, and Gilda Radner, these authors also scout out some unlikely comic resources, like the author of the biblical book of Exodus, the rabbinic writer of Genesis Rabbah, and the party records star Belle Barth. Without forcing any of these characters into a preconstructed mold, the scholars who contributed to this collection allow readers both to discern the common features that make up “Jewish humor” and to delight in the individualism and eccentricities of the many figures whose lives and accomplishments are narrated here. Because these essays are written in a clear, jargon-free style, they will appeal to everyone—even those who don’t usually crack a smile!